Efek Perasan Rimpang Kunyit (Curcuma longa L.) Terhadap Gambaran Epitel Lambung Mencit yang Diinduksi Indometasin - Shabrina, Annisa Firra; Carolia, Novita; Tjiptaningrum, Agustyas (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2024)
Background: Gastric ulcers are stomach lesions characterized by depleted mucosa with the defect extending into the submucosa or muscularis propria. Gastric ulcers could be caused by the use of Indomethacin as an analgesic drug. Turmeric rhizome is a herbal plant that contains curcumin which has been suspected to play a role in gastric ulcer prevention. Objective: The aim of this study was to perceive the effect of turmeric rhizome juice with concentrations of 100%, 75%, and 50% on indomethacin-induced gastric epithelium image in mice. Methods: This experimental study with a Post Test Only Control design was conducted by using 25 samples of male ddY mice for 3 days intervention. Samples were divided into 5 groups, two control groups, and three intervention groups. The organ samples had been observed by assessing the gastric epithelium injury of mice on the antrum under a microscope with an objective lens 100x for eight fields of view. Results: The Kruskal-Wallis test had been used for analysis and showed a p-value of 0,025 which means it had a significant difference. Turmeric juice with concentrations of 100%, 75%, and 50% showed different effects on mice gastric epithelium image induced by Indomethacin (18 mg/kg). Conclusion: There were different effects of turmeric juice on gastric epithelium image induced by Indomethacin in mice.